The Effects of Human Resource Management Practices on Job Performance Among Non-Teaching Staff of Mindanao State University General Santos City - Dindang, Ronairah D. (International Journal of Research in Interdisciplinary Studies, 2025)
Human resource management (HRM) is a distinct approach to employment management that aims to gain a competitive edge by strategically developing a highly devoted and capable workforce using a combination of cultural, structural, and individual techniques (Storey, 2001). This study determined the effect of human resource management practices in terms of recruitment and selection, training and promotion, compensation and incentives, and performance appraisal on the performance of non-teaching staff in Mindanao State University in terms of time management, task accomplishment; responsibility, and creativity. The study also determined the issues and challenges encountered in human resource management practices on the job performance of the administrative staff of MSU-GSC. The study used a mixed methodology using survey research and semi-structured interviews. All in all, there were 250 employees classified as casual and permanent who participated in the study. Findings revealed that the total mean in recruitment and selection is 3.50 which is interpreted to be at the high level. This means that recruitment and selection is highly practiced by the human resource management office. The total mean of training and promotion is 3.51. This result is interpreted to be high level. It means that the staff are attended the training and development activities that may help them find solutions to the challenges in the office as well as the remedies to the work assigned. As to the compensation and incentives, the total mean is at 3.28 with a verbal description of moderate. Lastly, the total mean for performance appraisal is 3.76 at high level. The results of the study led to the rejection of the null hypothesis that there is no significant relationship between the non-teaching staff job performance and the human resource management practices. Human Resource Management Practices are the most critical factor for every organization. Non-teaching staff at MSU – GSC place a greater emphasis on work quality and long-term growth. Non-teaching staff works hard to improve and qualify for higher-level roles in the future. Lastly, if the non-teaching staff are happy with their work, they will build and sustain a high level of performance. Employee performance management improves